Integrated Emergency, Nursing, and Family Medicine Approaches to the Recognition and Management of Adrenal Crisis - Alenazy, Badrea Asri; Ashamlani,KhuludSaleh; Alotaibi, Sultan Daaj; Bajawi, Khalid Abdullah Mudaysh; Alhumaidan,LawahithMohammad; Alzahrani,AhmedSaeed; Alshehab, Maryaim Yousef; Aldossari, Khalid Mohammed D; Alzahrani,ZahraAli; Almaghrabi,AeshahOmarMusayyab; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Adrenal crisis is a life-threatening endocrine emergency caused by a severe deficiency of cortisol, often triggered by physiologic stress in individuals with underlying adrenal insufficiency. Despite being treatable, it carries a significant mortality rate, estimated at 0.5 deaths per 100 patient-years, primarily due to delays in recognition and intervention. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to outline the integrated, multidisciplinary approach required for the prompt recognition, emergency management, and long-term prevention of adrenal crisis, emphasizing roles across emergency medicine, nursing, and family medicine. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Management is centered on immediate parenteral glucocorticoid administration (100mg hydrocortisone IV/IM) and aggressive fluid resuscitation with isotonic saline. This is coupled with correction of hypoglycemia and electrolyte imbalances. Diagnosis relies on clinical suspicion based on a history of adrenal insufficiency, chronic steroid use, or presentation with refractory hypotension, and is supported by laboratory findings (e.g., hyponatremia, hyperkalemia, hypoglycemia). <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Prompt treatment leads to rapid clinical improvement, but delayed intervention results in high mortality and complications such as seizures, arrhythmias, and multi-organ failure. Patient education on "sick day rules" (stress-dose steroids) and access to emergency hydrocortisone injection kits are critical for preventing recurrent crises. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Adrenal crisis remains a preventable cause of death. Optimal outcomes depend on a high index of suspicion, immediate empiric therapy, and a coordinated interprofessional team strategy to ensure seamless care from emergency response to long-term community management.